Determination of tectonic and nontectonic vertical motion rates of the North China Craton using dense GPS and GRACE data. (15th September 2022) - Wang, Dongzhen; Zhao, Bin; Li, Yu; Yu, Jiansheng; Chen, Yi; Zhou, Xiaohui
Graphical abstract: Highlights: The elastic (un-)loading response to mass changes is calculated using GRACE data. The average estimated tectonic uplift rate in the mountain areas is 1.37 ± 0.6 mm/yr. The maximum land subsidence rate in the North China Plain is 72.0 ± 1.2 mm/yr. A high-resolution water mass variation model is needed. Abstract: Previous geodetic vertical observations show that both uplift and subsidence occur in the North China Craton. While significant land subsidence occurs in the North China Plain, uplift is observed in the surrounding mountain areas. However, previous studies neither separate the tectonic and nontectonic vertical motions nor correct for elastic response to near surface mass changes. Here, we reply on the more GPS data from 1999 to 2020 and GRACE data from 2002 to 2020 to estimate the vertical motion rates. After removing the elastic (un-)loading deformation due to near surface mass variations, we obtain the tectonic uplift rates at GPS stations built on bedrock in the mountain areas like the Shanxi Plateau and land subsidence rates mainly in the North China Plain. The tectonic rock uplift mainly occurs in the Shanxi Plateau, Yanshan Montains, Shandong Peninsula and Dabie orogen, with an average uplift rate of 1.37 ± 0.6 mm/yr, which is larger than the long-term geological uplift rate. The land subsidence mainly concentrates in the North China Plain, Shanxi Graben, and Jiangsu province with the maximum subsidence rate of 72 ± 1.2 mm/yr. The mismatch between the geodetic and geological uplift rates suggests that a high-resolution water mass loss in the North China Plain is needed.